How would the parties' tax and spending plans affect Scotland and Wales? - David Phillips (Institute for Fiscal Studies (IFS), 2024)
This "explainer" looks at how the parties' proposals would affect Scotland and Wales, covering tax, spending, public finances and the constitution.
Keywords: 330; Government finances and spending; Taxes and benefits; Benefits; Devolution; Devolved government finances; Fiscal rules and frameworks; Government spending; Income taxes; National Insurance contributions; Public finance; Public sector; Scottish independence; Tax; Wales; Scotland